Norwich terriers possess a greater vertebral heart scale than the canine reference value. Issue 1 (1st October 2019) - Taylor, Colin J.; Simon, Bradley T.; Stanley, Bryden J.; Lai, Grace P.; Thieman Mankin, Kelley M.
Abstract: Previous studies have demonstrated evidence that normal reference ranges for radiographic vertebral heart scale values can vary among dog breeds. The purpose of this retrospective, observational study was to determine whether the normal vertebral heart scale values published by Buchanan and Bücheler for lateral radiographs are applicable to the Norwich terrier. Secondary objectives were to determine if clinical signs of respiratory disease, age, sex, weight, body condition score, recumbency, or thoracic depth‐to‐width ratio had any influence on vertebral heart scale measurements in this breed. The electronic medical record systems of two universities were reviewed and Norwich terriers were included in the study if they had orthogonal thoracic radiographs performed and no historical or radiographic evidence of cardiopulmonary disease. A vertebral heart scale was calculated for each patient. Sixty‐one client‐owned, Norwich terrier dogs with no clinical signs of cardiovascular disease were evaluated. The vertebral heart scale for Norwich terriers without evidence of cardiac disease (10.6 ± 0.6) was found to be significantly greater than the canine reference value of 9.7 ± 0.5 initially established by Buchanan and Bücheler. No significant correlation was found between clinical signs of respiratory disease, sex, age, thoracic depth‐to‐width ratio or lateral recumbency, and vertebral heart scale. Norwich terriers with a body condition score ≥6 had a significantly higher vertebral heart scale than those with a body condition score ≤5. Breed‐specific ranges and body condition scores need to be considered when interpreting vertebral heart scale values for Norwich terriers.